EXPLORING THE IMPACT OF SALINITY STRESS ON DIVERSE WINTER WHEAT VARIETIES (Conferencea, 2024)
To provide the population with quality food products, great attention is being paid to agricultural sectors. In order to satisfy the population's need for high-quality food products, the main goal is to obtain a high and high-quality harvest from winter wheat varieties even in the conditions of soil salinity. Climate change inevitably leads to the deterioration of the ecological situation, and the drying of fertile soils, in turn, leads to increased salinity, which causes large crop losses.